2012
DOI: 10.1590/s1516-14392012005000148
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic and equilibrium study of zinc removal by Brazilian bentonite clay

Abstract: This paper aimed to study the removal of zinc using bentonite clay from the Northeastern Brazil, as an adsorbent. A study of the clay subjected to thermal and chemical treatment was performed in order to evaluate the optimization of the adsorption capacity of this material. For the evaluation of the kinetic equilibrium of the process, experimental tests were carried out in a finite bath system. The maximum amount of metal adsorbed was 0.151 mEq of metal per gram of calcined clay and 0.257 mEq of metal per gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…XRD diffractograms indicated characteristic peaks of Na-montmorillonite at 2θ 7.57°, 20°, and 28°, respectively. 27,28 The peak at 2θ = 20°, characteristic for nonbasal reflections (02, 11), was present for all nanocomposites, indicating that the crystalline layered structure was not affected by the modification process. 29,30 The 2θ value at 28°was attributed to (005) reflection.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…XRD diffractograms indicated characteristic peaks of Na-montmorillonite at 2θ 7.57°, 20°, and 28°, respectively. 27,28 The peak at 2θ = 20°, characteristic for nonbasal reflections (02, 11), was present for all nanocomposites, indicating that the crystalline layered structure was not affected by the modification process. 29,30 The 2θ value at 28°was attributed to (005) reflection.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…The parameters obtained for the non-linear Langmuir-Freundlich equations are shown in Table V. Compared to some other adsorbents, such as Bofe clay with a q max of 4.39 mg.g -1 [66], and a lateritic clay with a q max of 5.60 mg.g -1 [67], both for heavy metals adsorption from aqueous solution, the values for maximum adsorption capacity for Zn 2+ obtained in this study were superior. Table V shows the calculated values of the Langmuir and Freundlich model parameters.…”
Section: Source Dfmentioning
confidence: 73%
“…In the present study, we observed a clay expansion of approximately 2-to 3-fold within the core tube system. The negative charge on the structure of clay minerals attracts cationic metals (Babel & Kurniawan, 2003), and thus clay has been shown to be effective for removing Zn and other metal ions (e.g., Pb 2+ , Al 3+ ) from aqueous solutions (Brummer, 1986;Pereira de Araujo et al, 2013;Ryan et al, 2009;Shi et al, 2009). Bothe and Brown (1999) evaluated bentonite clay for Zn removal and found that its sorption capacity was 52.9 mg of Zn 2+ g −1 bentonite and fit the Langmuir model.…”
Section: Effects Of Capping Materials On Zn Fluxmentioning
confidence: 99%